Jack Hunter, "Ecology and Spirituality: A Brief Introduction" - Grieve-Carlson, Timothy (Journal for the study of religion, nature and culture, 2025)
Jack Hunter, Ecology and Spirituality: A Brief Introduction (Ceredigion, Wales: Sophia Centre Press, 2023), 213 pp., $ 24 (pbk), ISBN: 978-1-907767-23-4.